Enhancing Protein Density and Nutritional Value of Pumpkin–Skipjack Tuna Biscuits as a Complementary Food for Stunted Toddlers - Juniarti, Rizky Auliah; Riswanti, Riswanti; Putri, Indah Perdana (Utan Kayu Publishing, 2025)
This experimental study evaluated pumpkin–skipjack tuna composite biscuits as a locally adaptable complementary snack for stunted toddlers. Using a completely randomized design with one control and four formulations, we quantified protein and iron and assessed sensory acceptance with 20 semi-trained adult panelists. Compared with the pumpkin-only control (3.37% protein), the best formulation (D: 461 g pumpkin; 125 g skipjack tuna) achieved 9.07% protein—an absolute gain of 5.70 percentage points and a 169% relative increase (t-test p = 0.025). Iron differed nonsignificantly across groups (e.g., formulation D descriptively higher), indicating matrix effects that warrant bioavailability testing. Focusing on key outcomes rather than detailed hedonic scores, we found formulation D to be most acceptable overall. A practical translation suggests a 50 g serving could supply 35–40% of the toddler protein RDA, while iron contributions remain uncertain pending bioavailability evidence. The sensory panel comprised adults (not toddlers), so future caregiver-assisted trials are needed to confirm end-user acceptance and safe portion sizes. In sum, moderate inclusion of skipjack tuna flour meaningfully enhances protein density without compromising acceptance, supporting the development of shelf-stable, culturally familiar snacks for nutrition programs targeting stunting; iron claims should remain cautious until bioavailability is established. Abstrak. Penelitian eksperimental ini mengevaluasi biskuit komposit labu–tepung ikan cakalang sebagai camilan pendamping yang dapat diadaptasi secara lokal bagi balita stunting. Dengan rancangan acak lengkap yang mencakup satu kontrol dan empat formulasi, kami mengukur kadar protein dan zat besi serta menilai penerimaan sensori menggunakan 20 panelis dewasa semi-terlatih. Dibandingkan kontrol berbasis labu saja (protein 3,37%), formulasi terbaik (D: 461 g labu; 125 g tepung ikan cakalang) mencapai protein 9,07%—kenaikan absolut 5,70 poin persentase dan peningkatan relatif 169% (uji t, p = 0,025). Kadar zat besi tidak berbeda signifikan antar kelompok (meski formulasi D lebih tinggi secara deskriptif), menunjukkan kemungkinan adanya efek matriks yang memerlukan uji bioavailabilitas. Berfokus pada luaran kunci alih-alih rincian skor hedonik, formulasi D menunjukkan penerimaan keseluruhan terbaik. Secara praktis, takaran saji ±50 g diperkirakan memenuhi ≈35–40% Angka Kecukupan Gizi protein balita, sementara kontribusi zat besi masih belum pasti sebelum bukti bioavailabilitas tersedia. Panel sensori terdiri atas orang dewasa (bukan balita), sehingga uji coba dengan pendampingan pengasuh diperlukan untuk mengonfirmasi penerimaan pengguna akhir dan keamanan takaran saji. Disimpulkan, inklusi moderat tepung ikan cakalang secara bermakna meningkatkan densitas protein tanpa menurunkan penerimaan, mendukung pengembangan camilan stabil-simpan yang akrab secara budaya bagi program gizi untuk penurunan stunting; klaim terkait zat besi perlu tetap hati-hati hingga bioavailabilitas terverifikasi.